Barriers to Inclusion and Successful Engagement of Parents in Mainstream Services: Evidence and Research. Issue 3 (19th August 2014) - La Placa, Vincent; Corlyon, Judy
Abstract : Purpose: This article reviews the current evidence base on barriers to inclusion and successful engagement of parents in mainstream preventive services. Design/methodology/approach: Evidence was generated using a narrative review which uses different primary studies from which conclusions are produced into holistic interpretations. It provides an interpretative synthesis of findings based upon an exhaustive inclusion and exclusion criteria and systematic selection of literature. Findings: The paper identifies barriers to successful engagement as: structural; social and cultural; and suspicion and stigma. In terms of successful engagement, it identifies personal relations between staff and service users, practical issues, service culture, consultation, information and targeting, service delivery, and community development and co-production approaches. Research limitations/implications: The paper demonstrates that the evidence base is limited and not adequately theoretically grounded. It argues for more research based within a pragmatic approach, which is more theoretically and epistemologically informed. Practical implications: The paper demonstrates that more theoretically and epistemologically informed research needs to be addressed in order to design mainstream services on behalf of service practitioners and researchers. Originality/value: Such an approach would assist policy makers and practitioners to develop interventions to reduce potential barriers and facilitate successful engagement and is grounded within users' experiences. It would also reflect the complexity of working within a late modern environment, attend to the multiple needs of users, and address the complex layers intrinsic to the construction and reproduction of services, as well as widening the current evidence base.